Supply chain knowledge work: should we restructure the workforce for improved agility?. (26th November 2007) - Butcher, Tim
Responsive supply networks must shift from traditional hierarchies to more holistic supply chain-spanning management systems to remain competitive. Knowledge work is fundamental to this transition, but little is written about the roles of knowledge workers in logistics and supply chain management and their influence on agility. Adopting a Socio-Technical Systems approach, this research analyses empirical case study data to identify and evaluate supply chain knowledge workers. We find that supply chain knowledge workers maintain supply chain performance and improve it by compensating for inherent operational instabilities and changes in supply and demand. Hence, knowledge workers contribute to the adaptability, responsiveness, agility and resilience of supply chains. We propose that, given the opportunity, supply chain knowledge workers could enable transition to the emerging sense and respond paradigm through improved utilisation of their expertise. This research has implications for supply chain design, practice and education. Thus, further research is recommended to develop work systems that encourage greater scope for supply chain knowledge work.